Quantitative analysis of lactose and lactulose in urine by high performance liquid chromatography for determination of intestinal lactase activity (Medical Journal of Indonesia, 2003)
Determination of intestinal lactase activity is directly done by measuring its activity in intestinal epithelium. This is an invasive method and ethically can not be done in healthy infants. Indirectly, determination of lactase activity, stated as excretion and ingestion ratio of lactose and lactulose, needs 30 hours hospitalized infants. The aim of this study was to look for a method for determination of lactase activity which is not invasive and not necessary hospitalized. Using this method lactose and lactulose were given as a single oral load after 2 hours fasting. Urine were collected for 5 hours starting from consuming sugar solution and then lactose and lactulose concentration in the urine were measured by High Performance Liquid Chromatography. The results showed single oral load of lactose and lactulose can be used for determination of lactase activity in infant and the infants were observed only for 7 hours. (Med J Indones 2003; 12: 8-12) Keywords: Lactase activity, Lactulose, Lactose, High Performance Liquid Chromatography